2017
DOI: 10.1038/s41598-017-02451-3
|View full text |Cite
|
Sign up to set email alerts
|

Tail tubular protein A: a dual-function tail protein of Klebsiella pneumoniae bacteriophage KP32

Abstract: Tail tubular protein A (TTPA) is a structural tail protein of Klebsiella pneumoniae bacteriophage KP32, and is responsible for adhering the bacteriophage to host cells. For the first time, we found that TTPA also exhibits lytic activity towards capsular exopolysaccharide (EPS) of the multiresistant clinical strain of Klebsiella pneumoniae, PCM2713, and thus should be regarded as a dual-function macromolecule that exhibits both structural and enzymatic actions. Here, we present our crystallographic and enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 53 publications
(48 reference statements)
3
40
0
1
Order By: Relevance
“…TTPB forms the end of the tail below TTPA [15]. TTPA in Klebsiella pneumoniae bacteriophage KP32 has also been shown to have enzymatic activity to hydrolyze bacterial polysaccharides [42,43], but the role of TTPA in phage adsorption has not been experimentally shown. To the best of our knowledge, this study is the first time that tail structures TTPA and TTPB have been demonstrated to serve as ligands that recognize the conserved Vibrio receptor Vp0980 to mediate phage adsorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TTPB forms the end of the tail below TTPA [15]. TTPA in Klebsiella pneumoniae bacteriophage KP32 has also been shown to have enzymatic activity to hydrolyze bacterial polysaccharides [42,43], but the role of TTPA in phage adsorption has not been experimentally shown. To the best of our knowledge, this study is the first time that tail structures TTPA and TTPB have been demonstrated to serve as ligands that recognize the conserved Vibrio receptor Vp0980 to mediate phage adsorption.…”
Section: Discussionmentioning
confidence: 99%
“…TTPA forms the attachment site for the side fibres, while TTPB (also called a nozzle) serves as an adaptor for mounting additional functions [15,40,41]. Although TTPA and TTPB have been implicated as phage adhesins for adsorption to the host [42,43], it has not been shown whether they bind specific receptors to mediate the adsorption. We expressed GST-tagged TTPA and TTPB and performed pulldown assays with His-tagged Vp0980.…”
Section: Identification Of Phage Proteins That Bind Vp0980mentioning
confidence: 99%
“…The diversity of phage PDs results from the co-evolution of phages and 52 their host bacteria [10]. Previously, we have reported the preliminary results of biological activity 53 of the tail tubular proteins A of the phages KP32 and KP34 [8,9]. These proteins were called the 54 dual-function proteins due to their structural and hydrolytic features related to binding and [11,5].…”
mentioning
confidence: 99%
“…encoded in the open reading frames of phage structural proteins and thus were considered as 51 structural proteins [7][8][9]. The diversity of phage PDs results from the co-evolution of phages and 52 their host bacteria [10].…”
mentioning
confidence: 99%
“…For example, tail tubular protein A (TTPA), a structural tail protein of phage KP32, was shown to have additional polysaccharide depolymerase activity. Pyra et al (2017) cloned and expressed TTPA in E. coli and determined its enzymatic activity by agar spot tests on lawns of K. pneumoniae PCM2713, which produced translucent zones of reduced growth. Subsequent microscopic analysis of treated and untreated K. pneumoniae revealed cells treated with TTPA were stripped of their capsules.…”
Section: Polysaccharide Depolymerasesmentioning
confidence: 99%